2012
DOI: 10.1007/s00410-012-0721-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of water on intergranular mass transport: new insights from diffusion-controlled reaction rims in the MgO–SiO2 system

Abstract: We experimentally investigate the effect of water on intergranular mass transport. The growth of enstatite single rims between forsterite and quartz and forsterite-enstatite double rims between periclase and quartz was performed at 1,000°C and 1.5 GPa for incremental water-solid fractions ranging from 0 to 5 wt%. A kinetics analysis based on time series ranging from 8 min to 18 h at 1 wt% H 2 O demonstrates that the growth of both the single and double rims is controlled by the transport of the chemical compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 30 publications
1
31
2
1
Order By: Relevance
“…However, according to Chantel et al (2016), the very low amounts of melt that could be expected in the pure olivine aggregate (< 0.1%) would not wet the grain boundaries, as reflected in the very high EC compared to samples with a low added basalt fraction (Table 2 and Fig. SI 7) even though intergranular mass transport is strongly influenced by minor amounts of hydroxyl as proven by the work of Gardés et al (2012). It is shown that activation energy of diffusion in hydrous-saturated grain boundaries is reduced compared to dry grain boundaries.…”
Section: Melt Fraction Determinationmentioning
confidence: 99%
“…However, according to Chantel et al (2016), the very low amounts of melt that could be expected in the pure olivine aggregate (< 0.1%) would not wet the grain boundaries, as reflected in the very high EC compared to samples with a low added basalt fraction (Table 2 and Fig. SI 7) even though intergranular mass transport is strongly influenced by minor amounts of hydroxyl as proven by the work of Gardés et al (2012). It is shown that activation energy of diffusion in hydrous-saturated grain boundaries is reduced compared to dry grain boundaries.…”
Section: Melt Fraction Determinationmentioning
confidence: 99%
“…Fluid-saturated grain boundaries provide such a means for extensive mass transport by providing diffusional shortcuts relative to dry systems (Gardés et al 2012;Rubie 1986). A fluid capable of forming an interconnected network along grain boundaries is thus important for regional-scale mineral replacements (Harlov et al 2005).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Natural and experimental data reveal that Si-rich melts [56,57], or aqueous [58] or supercritical fluids [59] are released from the underlying subducted oceanic slab into the sub-arc region driving the dissolution of mantle olivine and the neoformation of pyroxenes and Al-phases in a range of pressures between 0.8 and 3.4 GPa [60][61][62][63][64][65][66][67][68]. Experimental results of Grant et al [69] at 800 MPa suggest that neoblasts of orthopyroxene and clinopyroxene form at a relatively narrow temperature range of around 800 to 900 • C (with few exceptions up to 1100 • C).…”
Section: Origin Of Ol-orthopyroxenite and Websteritementioning
confidence: 99%